Hubungan Kecerdasan Emosional Dengan Hasil Belajar Biologi Peserta Didik Kelas XI MIA SMA Negeri 3 Makassar - Nur Asma; Nurhayati B; Muhiddin Palennari (UNM Journal of Biological Education, 2018)
This study was a descriptive correlational research that aimed to know the correlation between emotional intelligence and students’ biology learning outcomes. The population in this study was all of the students of class XI MIA SMA Negeri 3 Makassar as many as 256 people. The research samples were 158 students chose by purposive sampling. Data collection was conducted in March of 2018 on academic year 2017/2018. Emotional intelligences’ data obtained by survey methode using questionnaire and students’ biology learning outcomes obtained by multiple-choice test. Data of research analyzed with descriptive statistic to know the emotional intelligence and students’ biology learning outcomes, and inferensial statistic that are normality test using Kolmogrov-Smirnov test, linearity test using ANOVA Table analysis and correlation test using Pearson Product Moment to know the correlation between emotional intelligence and students’ biology learning outcomes. The results showed that: (1) the dominant learners had emotional intelligence in medium category with percentage 64,56%, (2) the dominant learners had biology learning outcomes in very low category by percentage 61,39%, (3) there was a correlation between emotional intelligence and students’ biology learning outcomes proved by coefisien correlation number < 0.05 as amount as 0.000. The coefisien correlation amount of this research was 0,692 showed that the correlation category was strong.